Analysis System Social Interaction of Otaku in the movie "Densha Otoko" Directed Shousuke Murakami - Raharja, Endra (Jurnal Ilmiah Mahasiswa FIB, 2013)
Densa Otoko is a film directed by Shousuke Murakami. The film described about Otako who only spend their time for working and they always walked around Akihara for viewing and collecting figures anime favorite. The writer interested in the movie about social interaction of Otaku. The one approach that can be done for focusing on the characterization and social interaction system, better known as the sociology of literature. The theory that the writer used for analyzing this film is the theory of sociology, communication, otaku and mise-en-scene. The results of this study are perceived convenience Densha Otoko to socialization proses with internet that makes life to be alone and more likely to choose a virtual life. Meeting with Hermes made ​​Densha Otoko’s life changing and have a desire to live the life of a human being. Densha Otoko desire to live in the real world due to various factors, including the factors identified, factor of sympathy, and the factor of suggestion, while interacting with other human beings  Densha Otoko doing some form of cooperation, accommodation and assimilation. Densha Otoko effort in interacting with other human beings doing a process of cybernetic communication, cognitive dissonance, and a process of rhetoric. Changing process made Densha Otoko certainly will not effective if there are many factors such as the factors that can facilitate the assimilation among others, contact with other cultures, respect for one's work and the desire to progress, tolerance, open system of society, the public dissatisfaction to certain areas of life, future orientation, as well as a strong desire to improve his life. In the next analyze of study the writer suggest for choosing this movie with other approaches with the goal of enriching the appreciation of the literary work.